Recent Advances in Endothelial Progenitor Cells Toward Their Use in Clinical Translation - Keighron, Cameron; Lyons, Caomhán J.; Creane, Michael; O'Brien, Timothy; Liew, Aaron (Frontiers in Medicine, 2018)
Since the discovery of Endothelial Progenitor Cells (EPC) by Asahara and colleagues in 1997, an increasing number of preclinical studies have shown that EPC based therapy is feasible, safe and efficacious in multiple disease states. Subsequently, this has led to several, mainly early phase, clinical trials demonstrating the feasibility and safety profile of EPC therapy, with the suggestion of efficacy in several conditions including ischemic heart disease, pulmonary arterial hypertension and decompensated liver cirrhosis. Despite the use of the common term ‘EPC’, the characteristics, manufacturing methods and subset of the cell type used in these studies often vary significantly, rendering clinical translation challenging. It has recently been acknowledged that the true EPC is the endothelial colony forming cells (ECFC). The objective of this review was to summarize and critically appraise the registered and published clinical studies using the term ‘’EPC’’, which encompasses a heterogeneous cell population, as a therapeutic agent. Furthermore, the preclinical data using ECFC from the PubMed and Web of Science databases were searched and analyzed. We noted that despite the promising effect of ECFC on vascular regeneration, no clinical study has stemmed from these preclinical studies. We showed that there is a lack of information registered on www.clinicaltrials.gov for EPC clinical trials, specifically on cell culture methods. We also highlighted the importance of a detailed definition of the cell type used in EPC clinical trials to facilitate comparisons between trials and better understanding of the potential clinical benefit of EPC based therapy. We concluded our review by discussing the potential and limitations of EPC based therapy in clinical settings.